2017
DOI: 10.1007/s11240-017-1300-x
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of mature Quercus ilex L. trees by axillary budding

Abstract: This paper reports the successful micropropagation of mature Quercus ilex trees known as reluctant to in vitro propagation. Crown branch segments collected from 30 and100 year-old trees were forced in order to promote the production of sprouting shoots that were used as a source of explants for initiating the cultures. Sterilization was critical and required low-level disinfestation protocols. Six out of the eight mature genotypes attempted were successfully inoculated and then maintained in culture with varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 58 publications
2
33
1
Order By: Relevance
“…In Q. serrata, WPM with 2 mg·L −1 BA produced the highest number of shoots [31]. While highest shoot proliferation rate of Q. ilex was achieved by alternating 2 week long subcultures on much lower concentration of cytokinin, which was 0.1 mg·L −1 BA first, followed by 0.05 mg·L −1 BA, then 0.01 mg·L −1 BA plus 0.1 mg·L −1 zeatin [32]. The effect of genotype on the optimal protocol was shown to be one of the most serious limitations concerning the commercial micropropagation of oaks [21].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Q. serrata, WPM with 2 mg·L −1 BA produced the highest number of shoots [31]. While highest shoot proliferation rate of Q. ilex was achieved by alternating 2 week long subcultures on much lower concentration of cytokinin, which was 0.1 mg·L −1 BA first, followed by 0.05 mg·L −1 BA, then 0.01 mg·L −1 BA plus 0.1 mg·L −1 zeatin [32]. The effect of genotype on the optimal protocol was shown to be one of the most serious limitations concerning the commercial micropropagation of oaks [21].…”
Section: Discussionmentioning
confidence: 96%
“…The effect of genotype on the optimal protocol was shown to be one of the most serious limitations concerning the commercial micropropagation of oaks [21]. Other components such as sucrose concentration and agar brand also affected shoot proliferation in Q. ilex [32]. Other basal media, such as plant growth regulators can also be trialed, however only BA and IBA were chosen in this study as these two plant growth regulators were the most commonly used.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the proliferation of shoots established from mature material of holm oak is not influenced by the explant type (Martínez & al., 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our previous experience with adult holm oak material (Martínez & al., 2017a), the multiplication medium used consisted of WPM supplemented with 30 g L -1…”
Section: Shoot Multiplication Stagementioning
confidence: 99%
“…Vieitez et al ( 2009 ) reduced the incidence of STN in northern red oak ( Quercus rubra L.) cultures by supplementing medium with 3 mg/l (17.6 µM) AgNO 3 . Martínez et al ( 2017 ) found that AgNO 3 at 20 µM reduced the incidence of STN in evergreen oak ( Quercus ilex L.) cultures. Park et al ( 2016 ) found that the production of ethylene in rose ( Rosa hybrida cv.…”
Section: Plant Growth Regulators Affect Stnmentioning
confidence: 99%